2022
DOI: 10.7759/cureus.21610
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Prediction of Intracranial Meningioma Grade Using Conventional CT and MRI

Abstract: Preoperative diagnosis of tumor grade can assist in treatment-related decision-making for patients with intracranial meningioma. This study aimed to distinguish between high-grade and low-grade meningiomas using conventional CT and MRI. MethodologyWe retrospectively analyzed 173 consecutive patients with intracranial meningioma (149 low-grade and 24 high-grade tumors) who were treated surgically at the National Hospital Organization Kyushu Medical Center from 2008 to 2020. Clinical and radiological features, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
3
0
3
Order By: Relevance
“…Beyond this simple diagnosis, researchers have been using non-invasive imaging biomarkers to predict tumor grading, which affects patient treatment decisions and prognosis. In previous studies, several conventional and advanced MRI findings have been identified as suggestive of high-grade meningiomas [4,6,[14][15][16][17][18][19][20]. The imaging findings associated with high-grade meningiomas include higher degree of peritumoral edema, intratumoral necrosis, lower ADC values, heterogeneous enhancement, dural tail sign, irregular or poorly defined tumor margins, and blurred or irregular tumor-brain interface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond this simple diagnosis, researchers have been using non-invasive imaging biomarkers to predict tumor grading, which affects patient treatment decisions and prognosis. In previous studies, several conventional and advanced MRI findings have been identified as suggestive of high-grade meningiomas [4,6,[14][15][16][17][18][19][20]. The imaging findings associated with high-grade meningiomas include higher degree of peritumoral edema, intratumoral necrosis, lower ADC values, heterogeneous enhancement, dural tail sign, irregular or poorly defined tumor margins, and blurred or irregular tumor-brain interface.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is the most important imaging technique for the detection and preoperative evaluation of intracranial meningiomas. Previous studies have reported that preoperative MRI is useful for grading meningiomas and evaluating their histopathological characteristics by analyzing imaging findings such as heterogeneous enhancement, marked peritumoral edema, irregular tumor margins, and bone destruction [4][5][6]. Despite these findings, the image patterns of different grades of meningiomas can often mimic each other, and the usefulness of tumor grading using conventional MRI alone remains controversial [7].…”
Section: Introductionmentioning
confidence: 99%
“…cian con sospecha de malignidad. La clínica, el tamaño, el edema perilesional, la irregularidad y heterogeneidad, así como aspectos imagenológicos basados en el ADC, mostraron ser factores que aumentan la probabilidad de malignidad del meningioma; así como la localización fuera de base cráneo 38,39,40 . Dentro de las diferentes características el tamaño es el único que tuvo importancia estadística a la hora de la resección subtotal en nuestra serie 41 .…”
Section: Discussionunclassified
“…Парасагітальні менінгіоми (ПМ) трапляються в 24,3-38,6% спостережень. За даними зарубіжних авторів [5,10,11], порівняно з менінгіомами іншої локалізації ПМ схильніші до рецидиву (від 18 до 40%). Це пояснюється не лише топографо-анатомічним розташування пухлини щодо внутрішньочерепних структур, що ускладнює радикальне і безпечне хірургічне втручання [11,12].…”
unclassified
“…Частота виявлення менінгіом Grade II та III серед пухлин парасагітальної локалізації також вища. Більшість авторів [10,[12][13][14] указують на залежність рецидиву менінгіоми від статі пацієнта, характеру ураження верхнього сагітального синуса (ВСС) та радикальності видалення пухлини. За даними інших авторів [15], ризик рецидивування/ продовженого росту ПМ збільшується: 1) у 7,04 разу при початковому розмірі >54 мм; 2) у 5,57 разу за нерадикального видалення пухлини під час первинного втручання (Simpson ІІ-V); 3) у 10,1 разу при І-ІІ типі інвазії ПМ у ВСС та неповному видаленні пухлини (Simpson ІІ-V); 4) у 3,25 разу у пацієнтів чоловічої статі; 5) у 3,33 разу при ІV типі інвазії у ВСС (за M.P.…”
unclassified